The Role of Artificial Intelligence Applications in Developing Vocational Education; A Future Vision for Professional Training - Alorfi, Asma Thabet Mubarak; Alharbi, Maha Ouda Awad (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the role of Artificial Intelligence (AI) in reshaping and improving the quality of vocational education and professional training. It focused on identifying key challenges facing this sector amid rapid technological and labor market developments. The study adopted a descriptive-analytical approach, relying on a systematic review of literature and recent research on AI applications. The findings revealed cultural acceptance barriers and adaptation difficulties, in addition to ethical concerns and technical challenges related to infrastructure. The study highlighted the significant potential of AI in personalizing learning paths to meet individual learners’ needs, enhancing engagement and effectiveness. Achieving these benefits, however, depends on establishing clear regulatory frameworks, improving technical infrastructure, providing intensive teacher training programs, and fostering collaboration among all stakeholders. Numerical evidence (e.g., a 30% increase in student engagement in institutions that utilized adaptive AI systems compared to those using traditional methods) indicates that integrating machine learning algorithms into vocational education systems improved both training efficiency and learning outcomes. The study recommends prioritizing policy development and regulatory frameworks, updating curricula to include AI competencies, aligning educational systems with labor market needs through data analytics, and embracing a forward-looking vision for lifelong learning.
Keywords: Artificial Intelligence; Vocational Education; Professional Training; AI Ethics; Machine Learning Algorithms; Content Personalization